La educación sexual en el desarrollo integral de las personas con discapacidad de la Orquesta Tropical Son Especial del Ilustre Municipio de Loja, y la intervención del Trabajador Social - Espinosa Rengel, Daniela Briggitte (2018)
The present investigative work is part of a study carried out on "Sexual education in the integral development of people with disabilities of the Tropical Special Orchestra of the Illustrious Municipality of Loja, and the intervention of the Social Worker." Which was based on objectives clear, concrete and precise the same that allowed to sustain the main categories of analysis and verify that parents of people with disabilities have limited knowledge in sex education. The present field investigation exposes the relevant data through the quantitative interpretation and the qualitative analysis, which allowed to verify and sustain the investigated object. The scientific question was formulated How does the limited sexual education of the family influence the integral development of people with disabilities in the Tropical Special Son Orchestra of the Municipality of Loja, November 2016 - December 2017? and the intervention of the Social Worker. Where it was proposed as a General Objective: Contribute to the integral development of people with disabilities who are members of the Tropical Special Son Orchestra, through sexual education programs aimed at families. And as specific objectives; Basing theoretically and scientifically the categories of analysis that generate the object of study, for the development of research; Determine how the limited sexual education in the family influences the integral development of people with disabilities of the Tropical Special Son Orchestra; Design a proposal for social intervention with the families of people with disabilities of the Tropical Special Sound Orchestra that incorporates information and communication on sexual education. 5 For this investigative process the Methodology of Insertion in Reality was used with its phases and levels, as an instrument structured interview; the universe of research was 36 people, of which 28 are parents of the members of the Tropical Special Son Orchestra, 6 people with physical and visual disabilities, 2 pedagogical support professionals of the group, of which it was taken as a sample all the universe. Different findings were found within the investigative process, such as, the main cause that has caused the limited sexual education in the family of persons with disabilities of the Tropical Orchestra Son Especial is the lack of knowledge and lack of information about sexuality in people with disabilities. , consider that it is necessary to dialogue and inform their children about issues related to sexual education although they do not do so due to taboos that still exist on the subject, they prevent the generation of adequate sexual information. In addition, the direct requirement of the intervention of the Social Worker as an entity of change was found, which guides and contributes to the improvement of social groups through their professional intervention. Finally, the research carried out will contribute to the integral development of people with disabilities of the Orquesta Tropical Son Especial, through sex education programs aimed at families.